Recomposição espacial e social do tecido urbano portuense - o Bairro do Cerco do Porto enquanto espaço de análise - Paula Guerra (2000)
The topic under discussion in this paper lies within a broader analysis of the process of rebuilding social and spatial evidenced in Porto over the decades of 80 and especially 90. Thus, the 90 decade of XX century in terms of socio-spatial recomposition of urban space in Porto, has seen the emergence, by the local authority, of one intervention strategy in the restructuring of eastern zone of the city, including, in physical terms, Campanhã. Therefore, our choice in analytical terms is limited to the particular case in which the analysis assumes that area of the city and particularly in the Bairro Cerco do Porto, either by being present, either by seeking a greater delineation of analytical approach.